Preparation and Potential Catalytic Applications of Hierarchically Structured Zeolites with Macropores - Weissenberger, Tobias; Machoke, Albert; Reiprich, Bastian; Schwieger, Wilhelm (Advanced Materials Interfaces, 2021)
Hierarchically structured zeolites can mitigate problems arising from the slow transport in the micropores, such as diffusion limitations. Hence, a manifold of different preparation methods for hierarchical zeolites have been developed over the years and the corresponding zeolites showed superior performance due to enhanced mass transport caused by higher diffusivities in the additional pore system and reduced diffusion path length in the micropores. The dimensions of the additional secondary “transport” pores in these materials is a major factor affecting their diffusion properties and consequently their catalytic performance. Interestingly almost all reports focus on the generation of additional mesopores and study of catalytic performance of mesoporous zeolites. Larger macropores with pore diameters of more than 50 nm, however, have some intrinsic advantages over mesopores that make them very attractive for catalytic applications. In the last years, methods for the preparation of zeolites and zeolite composites with additional macropores have been developed. These developments have brought about a novel and promising class of hierarchically structured materials; zeolites with macropores. This review gives an overview about different preparation routes for zeolites with inter or intra crystalline macropores as well as zeolite composites with macropores and summarizes the first studies regarding catalytic their performance.
CRIS-Team Scopus Importer:2021-02-05
Keywords: catalysts; hierarchical zeolites; hierarchically-ordered materials; macropores; zeolites